Binder-free anode with porous Si/Cu architecture for lithium-ion batteries. (15th March 2018) - Huang, Ting; Sun, Dingyue; Yang, Wuxiong; Wang, Hailong; Wu, Qiang; Xiao, Rongshi
Abstract: Binder-free porous Si/Cu architecture with the unique Cu walls wrapped Si/Cu porous network as lithium-ion battery anode was fabricated by laser remelting, diffusion bonding and dealloying processes. The porous network had enough space to allow for the large expansion of Si during lithation. The Cu walls and Cu skeletons could prevent loss of electrical contact between pulverized Si and current collector. The laser remelting influenced the Cu diffusion behavior during diffusion bonding, and was the most critical process for the fabrication of porous Si/Cu architecture. Graphical abstract: Image 1